KNOWLWEDGE OF TAXATION AND FISCUS SERVICE ON TAXPAYERS COMPLIANCE - Pratiwi Putri, Kartika; Meita Chandra Devi; Dodi Tisna Amijaya (Dinasti Publisher, 2020)
Achievement of Indonesia's tax income is faced with various obstacles so that it has not been able to meet the desired target. Compliance of taxpayers is an important factor for sources of state income to reach the state budget. The purpose this research is to determine wether there is a significant influence on knowledge of taxation and fiscus service against taxpayer compliance. This research uses a descriptive survey method involving 100 respondents of taxpayers through a questionnaire at Bandung tax office. The measured variable data included knowledge of taxation and fiscus services and continued by using multiple linear regression analysis. The results of the study prove that the level of knowledge of taxation and fiscus services affect partially tax compliance by 3.5% and fiscus services by 57.2%. Simultaneous is influenced by knowledge of taxation and fiscus services by 60.7% and by 39.3% influenced by other factors.